Elevated expression of H19 and Igf2 in the female mouse eye. - Björn Reinius (Public Library of Science (PLoS), 2013)
The catalogue of genes expressed at different levels in the two sexes is growing, and the mechanisms underlying sex differences in regulation of the mammalian transcriptomes are being explored. Here we report that the expression of the imprinted non-protein-coding maternally expressed gene H19 was female-biased specifically in the female mouse eye (1.9-fold, p = 3.0E-6) while not being sex-biased in other somatic tissues. The female-to-male expression fold-change of H19 fell in the range expected from an effect of biallelic versus monoallelic expression. Recently, the possibility of sex-specific parent-of-origin allelic expression has been debated. This led us to hypothesize that H19 might express biallelically in the female mouse eye, thus escape its silencing imprint on the paternal allele specifically in this tissue. We therefore performed a sex-specific imprinting assay of H19 in female and male eye derived from a cross between Mus musculus and Mus spretus. However, this analysis demonstrated that H19 was exclusively expressed from the maternal gene copy, disproving the escape hypothesis. Instead, this supports that the female-biased expression of H19 is the result of upregulation of the single maternal. Furthermore, if H19 would have been expressed from both gene copies in the female eye, an associated downregulation of Insulin-like growth factor 2 (Igf2) was expected, since H19 and Igf2 compete for a common enhancer element located in the H19/Igf2 imprinted domain. On the contrary we found that also Igf2 was significantly upregulated in its expression in the female eye (1.2-fold, p = 6.1E-3), in further agreement with the conclusion that H19 is monoallelically elevated in females. The female-biased expression of H19 and Igf2 specifically in the eye may contribute to our understanding of sex differences in normal as well as abnormal eye physiology and processes.